Fish oil-gelatin core-shell electrospun nanofibrous membranes as promising edible films for the encapsulation of hydrophobic and hydrophilic nutrients. (July 2021) - Liu, Lijie; Tao, Lina; Chen, Jiahui; Zhang, Ting; Xu, Jiamin; Ding, Mengzhen; Wang, Xichang; Zhong, Jian
Abstract: In this work, fish oil-gelatin core-shell electrospun nanofibrous membranes (ENMs) were explored as edible films for the encapsulation of hydrophobic fish oil and hydrophilic vitamin C (VC). The results demonstrated that fish oil-VC/gelatin core-shell ENMs could be successfully fabricated by a monoaxial emulsion electrospinning technique. The addition of VC didn't change core-shell structure but increased fragility of nanofibers. Excessive VC/gelatin mass ratios (≥4:20) increased the nanofiber adhesiveness during the storage at room temperature. No obvious chemical interactions occurred among fish oil, gelatin, and VC in the core-shell ENMs. VC addition decreased the loading capacity and had no obvious effects on encapsulation efficiency of fish oil in the ENMs. VC not only prevented lipid oxidation but also converted lipid hydroperoxides to other products during the electrospinning process. Fish oil-VC/gelatin core-shell ENMs were not disintegrated in ultrapure water but were disintegrated into particles in both gastric and intestinal fluids. The fish oil release from fish oil-VC/gelatin core-shell ENMs and disintegrated particles in the simulated intestinal phase of the gastrointestinal tract model and in the simulated intestinal model showed triphasic behaviors. This work provided a potential route to develop functional foods with encapsulation of both hydrophobic and hydrophilic nutrients. Highlights: Fish oil-gelatin/vitamin C (VC) core-shell electrospun nanofibers were fabricated. VC increased fragility of nanofibrous membranes and adhesiveness of nanofiber. VC addition decreased the loading capacity of fish oil in the membranes. VC addition could remove lipid hydroperoxides during electrospinning process. Membranes were disintegrated into particles in both gastric and intestinal fluids.